Characterization of high-temperature hierarchical porous mullite washcoat synthesized using aluminum dross and coal fly ash - Choo, Thye Foo; Mohd Salleh, Mohamad Amran; Kok, Kuan Ying; Matori, Khamirul Amin; Abdul Rashid, Suraya (MDPI, 2020)
Mixture of aluminum dross (AD) and coal fly ash (CFA) was used to produce high-temperature porous mullite for washcoat application. CFA is the combustion by-product of pulverized coal in a coal-fired power plant, while AD is a waste product produced in secondary aluminum refining. In this study, 80 wt% of AD and 20 wt% of CFA was used to prepare a mullite precursor (MP) via acid leaching and dry-milling. The precursor was coated on a substrate and subsequently fired at 1500 °C. The results showed that the precursor transformed to a hierarchical porous microstructure assembled by large interlocked acicular mullite crystals. The pore structures consisted of large interconnected open pores and small pores. The specific surface area of the mullite washcoat was 4.85 m2g−1 after heating at 1500 °C for 4 h. The specific surface area was compatible with the specific surface area of other high-temperature washcoats.